Study the reality of organizational climate in National Centers for Sport Talent Care from the trainers’ point of view - م.م. فاطمة الزهراء نفعت م.م. مروة خالد خزعل (الرياضة المعاصرة, 2021)
The importance of the study presents as it traces an important administrative component in the success of any institution, which is organizational climate, as it is an important source in the sustainability of the institution and the success of its work, especially institutions that are responsible for an important segment of society as a whole and the sports community in particular.